Host Immune Responses to Salivary Components - A Critical Facet of Tick-Host Interactions - Ali, Abid; Zeb, Ismail; Alouffi, Abdulaziz; Zahid, Hafsa; Almutairi, Mashal M.; Ayed Alshammari, Fahdah; Alrouji, Mohammed; Termignoni, Carlos; Vaz, Itabajara da Silva; Tanaka, Tetsuya (Frontiers in Cellular and Infection Microbiology, 2022)
Tick sialome is comprised of a rich cocktail of bioactive molecules that function as a tool to disarm host immunity, assist blood-feeding, and play a vibrant role in pathogen transmission. The adaptation of the tick’s blood-feeding behavior has lead to the evolution of bioactive molecules in its saliva to assist them to overwhelm hosts’ defense mechanisms. During a blood meal, a tick secretes different salivary molecules including vasodilators, platelet aggregation inhibitors, anticoagulants, anti-inflammatory proteins, and inhibitors of complement activation; the salivary repertoire changes to meet various needs such as tick attachment, feeding, and modulation or impairment of the local dynamic and vigorous host responses. For instance, the tick’s salivary immunomodulatory and cement proteins facilitate the tick’s attachment to the host to enhance prolonged blood-feeding and to modulate the host’s innate and adaptive immune responses. Recent advances implemented in the field of “omics” have substantially assisted our understanding of host immune modulation and immune inhibition against the molecular dynamics of tick salivary molecules in a crosstalk between the tick–host interface. A deep understanding of the tick salivary molecules, their substantial roles in multifactorial immunological cascades, variations in secretion, and host immune responses against these molecules is necessary to control these parasites. In this article, we reviewed updated knowledge about the molecular mechanisms underlying host responses to diverse elements in tick saliva throughout tick invasion, as well as host defense strategies. In conclusion, understanding the mechanisms involved in the complex interactions between the tick salivary components and host responses is essential to decipher the host defense mechanisms against the tick evasion strategies at tick-host interface which is promising in the development of effective anti-tick vaccines and drug therapeutics.